y-3x=4

3y+2x=1

y-3x=4

3y+2x=1

Tutors, please sign in to answer this question.

To solve a system of equations by substitution, solve one of the equations for one of the variables, then plug that result into the other equation.

We want to solve equation 2 for y, so we need to eliminate the x from that equation.

Solve equation 1 for x in terms of y:

y-3x = 4

-3x = -y + 4

**x = y/3 - 4/3**

Replace the x in equation 2:

3y + 2x = 1

3y + 2(y/3 - 4/3) = 1

Now the equation only has the variable y and you can solve it.

The answer to the original question is:

**y/3 - 4/3**